166k views
2 votes
Find the value of xFind the value of xFind the value of x

Find the value of xFind the value of xFind the value of x-example-1

1 Answer

5 votes

Answer:

x = 11

Explanation:


(x + 2)/(6) - \bigg( (11 -x )/(3) - (1)/(4) \bigg) = (3x - 4)/(12) \\ \\ (2(x + 2))/(2 * 6) - \bigg( (4(11 - x) - 1 * 3)/(3 * 4) \bigg) = (3x - 4)/(12) \\ \\ (2x + 4)/(12) - \bigg( (4 4 - 4x- 3)/(12) \bigg) = (3x - 4)/(12) \\ \\ (2x + 4)/(12) - \bigg( (41 - 4x)/(12) \bigg) = (3x - 4)/(12) \\ \\ \frac{2x + 4 - 41 + 4x}{ \cancel{12}} = \frac{3x - 4}{ \cancel{12}} \\ \\ 6x - 37 = 3x - 4 \\ \\ 6x - 3x = 37 - 4 \\ \\ 3x = 33 \\ \\ x = (33)/(3) \\ \\ \huge \red{ \boxed{ x = 11}}

User Mark Tielemans
by
5.3k points